Strategi Pemasaran Produk Kecantikan Berbahan Baku Tradisional: Desa Sukoanyar, Kecamatan Wajak, Kabupaten Malang - Chavid Moyo Jaladri; Ferra Eka Ramadhani; Erivina Lucy Kristian; Rofinus Agot; Muh. Arsyad; Nur Maghfiroh (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2023)
Currently, market competition is getting tougher, which requires the right marketing strategy to maintain sales and store existence. This study aims to determine the marketing strategy used in the Sukoanyar Wajak Traditional Cosmetic Business to face competitors and the effective marketing strategy used to deal with competitors in the Sukoanyar Wajak Traditional Cosmetic Business. The results showed that the marketing strategy for beauty products used in the Sukoanyar Wajak Traditional Cosmetics Business in dealing with competitors of similar products was not maximized; the constraints faced were only focused on one media used, namely traditional promotional media, friendly to consumers, and an effective strategy in dealing with good competitors. old competitors and new competitors, Sukoanyar Wajak Traditional Cosmetics Business must evaluate the product marketing strategy used by knowing the strengths and weaknesses of competitors.